Effect of High Fat and Cholesterol Diet on Total Blood Cholesterol Levels in Pregnant Wistar Rats - Desmawati Desmawati; Annisa Yuda Mahdiyah; Husnil Kadri (Majalah Kedokteran Bandung, 2023)
Hypercholesterolemia during pregnancy is a physiological condition resulting from increased insulin resistance, lipoprotein synthesis, and lipolysis in adipose tissue, which mobilizes lipids as an energetic substrate for fetal growth. Consumption of foods high in fat and cholesterol may lead to an increase in total blood cholesterol levels during pregnancy due to saturated fat and cholesterol contents that will increases the synthesis of lipoproteins in the blood. The objectives of this study were to determine the effects of high fat and cholesterol diet on the total blood cholesterol levels in pregnant Wistar rats. This study was a true experimental research using a randomized post-test-only control group design  conducted from November 2020 to October 2021on fourteen female Wistar rats that were divided into control and intervention groups. Cow brain was provided as the high fat and cholesterol diet and after the rats gave birth, blood was drawn from the heart. The total blood serum cholesterol levels were assessed  using Micro Lab 300 with the CHOD-PAP method and the data were analyzed using an independent t-test. This study showed that the mean total blood cholesterol levels for the control and treatment groups were 80.43±18.512 mg/dL and  142.57±24.786 mg/dL, respectively, which reflected a significant differences in the mean total blood cholesterol level between the control and treatment groups (p-value <0.01). In conclusion, a high fat and cholesterol diet affects the total blood cholesterol level in pregnant Wistar rats.